Device-Free AMR Crossing Detection Using LTE Signals for Smart Factory Applications - Hanae Otani; Tomoki Murakami; Kazuya Ohara; Yasushi Takatori; Tomoaki Ogawa (IEEE Access)
The Third Generation Partnership Project (3GPP) is currently discussing a new network for Integrated Sensing and Communications (ISAC). ISAC aims to enhance fifth and sixth-generation networks (5G/6G) by enabling simultaneous wireless sensing and communication while reducing cost, size, and power consumption by reusing existing wireless communication infrastructure. One use case of ISAC is the detection and collision avoidance of autonomous mobile robots (AMRs) in smart factories. We have also been studying the feasibility of ISAC under this use case to monitor AMR operations, such as transporting loads within a factory. This paper proposes a device-free AMR crossing detection method using Long-Term Evolution (LTE) signals for smart factory applications. In the proposed system, an AMR is assumed to be present at both the transmitting and receiving stations, and AMR crossing is detected from the acquired channel state information (CSI). However, CSI obtained from an actual system typically includes phase offsets due to frequency synchronization errors and receive timing offsets between the transmitting and receiving stations, which degrade the sensing accuracy. To address this issue, the proposed system reduces the phase offset using differential information between multiple antennas at the transmitting station and uses an offset removal method applicable to actual LTE reference signals. Through experiments with the proposed system, we confirmed that the phase offset could be eliminated using CSI phase. In additional, we demonstrated the AMR crossing frequency and period could be measured by analyzing the periodic fluctuations in the phase difference of the measured CSI.